Facts and figures : a graphical analysis of world energy up to 1987 (OPEC ViennaAT, 1988)
Provides statistics on the world energy industry. These relate to world primary energy needs; world oil and gas trends; world energy resources; OPEC flows and volumes; OPEC prices and values; trade flow from industrialized to developing countries and vice-versa. Compares GDP of several major economic regions of the world with that of the top ten donors of official development aid.
IDS